Dynastic Home Equity - Matteo Benetton; Marianna Kudlyak; John Mondragon (Institute of Labor Economics (IZA), 2022)
Using a nationally representative panel of consumer credit records for the US from 1999 to 2021, we document a positive correlation between child and parent homeownership. We propose a new causal mechanism behind this relationship based on parents extracting home equity to help finance their child's home purchase and quantify this mechanism in several ways. First, controlling for cohort, zip code, age, and the credit-worthiness of parents and children, we find that children whose parents extract equity are 60% more likely to become a homeowner than children whose homeowner-parents do not extract equity. Second, using an event study approach, we find that the increase in child homeownership occurs almost entirely in the year when parents extract equity. Third, using variation in equity extraction induced by households near leverage constraints, we find parental equity extraction increases the child's probability of becoming a homeowner by about five times. Our results highlight the importance of familial wealth for household wealth accumulation and housing wealth in particular. A back-of-the-envelope calculation suggests that dynastic home equity increases housing wealth inequality among young adults by 20%.
Keywords: G51; D64; E24; 330; home equity; intergenerational wealth; inequality; mortgages; housing; household finance